A Case Report on the Anxiolytic Properties of Nitrous Oxide during Labor. Issue 1 (19th January 2015) - Collins, Michelle
ABSTRACT: Widely used in Europe as a labor analgesic, nitrous oxide (N2O) is making a dramatic return in the United States. Valued for its analgesic properties, N2O also has anxiolytic characteristics. Fear and anxiety in childbirth have been associated with various negative effects, and N2O may have the potential to lessen these effects for some women. Women in the United States should have the option of using N2O during labor.